Rumination, substance use, and self-harm in a representative Australian adult sample - Tait, Robert; Brinker, J.; Moller, C.; French, D. (Wiley, 2013)
Background: There are few data on self-harm in the general population, especially examining the roles of rumination and substance use. Objectives: To evaluate the inter-relationships of rumination, self-harm, and potential mediating variables. Method: A cohort with follow-up every 4 years involving a random sample of adults aged 20–24 and 40–44 years (at baseline) living in Australia. The survey included items on three common forms of self-harm. Other measures included rumination, Goldberg Anxiety and Depression scales, substance use, coping style (Brief COPE), and demographic risk factors. Results: The sample comprised 2,184 women and 1,942 men with 287 self-harm cases (7.0%). Depression and coping style were significant mediators of rumination on self-harm for men, with depression being the only robust mediator for women. For males, age and education were also significantly associated, while for women, age, smoking, trauma, and sexual abuse were significant. Conclusions: Men and women differ on mediators of self-harm.